Додаткові послуги та інновації в соціокультурному просторі ресторанного бізнесу - Завгородня, О.Є. (Культура народов Причерноморья, 2014)
В статті розглянуто нововведення у сфері соціокультурного простору ресторанного бізнесу та охарактеризовано додаткові послуги, що пропонуються в сучасних закладах ресторанного господарства. Встановлено, що інновації відіграють велику роль в розвитку ресторанного бізнесу, є результатом зростання споживчого попиту та вимагають постійних змін. Запропоновано набір соціокультурних послуг, використовуючи які можна привабити відвідувачів до ресторанів та підвищити ефективність їх функціонування. До найбільш важливих віднесено впровадження креативних ІТ технології, використання QR-коду для ознайомлення відвідувачів із рестораном, мобільне приймання замовлень від відвідувачів, застосування технології кобрендингу. В статье рассмотрены нововведения в сфере социокультурного пространства ресторанного бизнеса и охарактеризованы дополнительные услуги, предлагаемые в современных заведениях ресторанного хозяйства. Установлено, что инновации играют большую роль в развитии ресторанного бизнеса, являются результатом роста потребительского спроса и требуют постоянных изменений. Предложено набор социокультурных услуг, используя которые можно привлечь посетителей в рестораны и повысить эффективность их функционирования. К наиболее важным отнесены внедрение креативных ИТ технологий, использование QR-кода для ознакомления посетителей с рестораном, мобильный прием заказов от посетителей, применение технологии кобрендинга. The research paper describes the innovations in the field of social and cultural space of the restaurant business. The additional services offered in themodern restaurant business establishments are characterized. It was found that innovations play an important role in the development of the restaurant business; they are the result of the growth in consumer demand and require constant changes. A set of social and culturals ervices was suggested using which you can attract visitors to restaurants and to increase the effectiveness of theiro peration. Introduction of creative IT technology, the use of a QR-codeto familiarize visitors with the restaurant, mobile taking of visitors’ orders, the use of co-branding technology, introduction of robots in the visitors’ servicing, using a variety of approaches to pricing policy of restaurants are referred to as the most important innovation services. The modern restaurant establishments use different innovative approaches to servicing its customers, as it affects the image and further profitability of their operations. Expediency of their application depends on the conditions of internal and external environment in which the restaurants operate, and is discussed at the senior management level. Despite some precautions, in the present conditions of the restaurant business the use of social and cultural services of innovative nature is a necessaryfactor for success in the operation of ideas of quality reception of visitors.